Ex vivo expansion of human Tfh-like cells from blood and inflammatory environments - Monteiro, Inês Filipa Pais (2020)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019